Rapid growth and genetic diversity retention in an isolated reintroduced black bear population in the central appalachians. Issue 5 (30th April 2015) - Murphy, Sean M.; Cox, John J.; Clark, Joseph D.; Augustine, Ben C.; Hast, John T.; Gibbs, Dan; Strunk, Michael; Dobey, Steven
ABSTRACT Animal reintroductions are important tools of wildlife management to restore species to their historical range, and they can also create unique opportunities to study population dynamics and genetics from founder events. We used non‐invasive hair sampling in a systematic, closed‐population capture‐mark‐recapture (CMR) study design at the Big South Fork (BSF) area in Kentucky during 2010 and Tennessee during 2012 to estimate the demographic and genetic characteristics of the black bear (Ursus americanus) population that resulted from a reintroduced founding population of 18 bears in 1998. We estimated 38 (95% CI: 31–66) and 190 (95% CI: 170–219) bears on the Kentucky and Tennessee study areas, respectively. Based on the Tennessee abundance estimate alone, the mean annual growth rate was 18.3% (95% CI: 17.4–19.5%) from 1998 to 2012. We also compared the genetic characteristics of bears sampled during 2010–2012 to bears in the population during 2000–2002, 2–4 years following reintroduction, and to the source population. We found that the level of genetic diversity since reintroduction as indicated by expected heterozygosity (HE) remained relatively constant (HE(source, 2004) = 0.763, HE(BSF, 2000–2002) = 0.729, HE(BSF, 2010–2012) = 0.712) and the effective number of breeders (NB) remained low but had increased since reintroduction in the absence of sufficient immigration (NB(BSF, 2000–2002) = 12, NB(BSF, 2010–2012) = 35). This bear population appears to be genetically isolated, but contrary to our expectations, we did not find evidence of genetic diversity loss or other deleterious genetic effects typically observed from small founder groups. We attribute that to high initial genetic diversity in the founder group combined with overlapping generations and rapid population growth. Although the population remains relatively small, the reintroduction using a small founder group appears to be demographically and genetically sustainable. © 2015 The Wildlife Society.